1967
DOI: 10.1002/bip.1967.360050906
|View full text |Cite
|
Sign up to set email alerts
|

X‐Ray diffraction of oriented amylose fibers. II. Structure of V amyloses

Abstract: SynopsisOriented amylose fibers in the V form were prepared and subjected to x-ray analysis. Unit cells and the probable space group of Pf21%'121 were determined for the V anhydrous and V hydrate forms of amylose; the analysis confirms previous predictions of these structures based on x-ray powder patterns. Chain folding in V amyloses is discussed in view of crystallographic evidence and folding experiments conducted with space-filling models. Reported also is evidence for amylose helices having diameters inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
0
1

Year Published

1968
1968
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 140 publications
(72 citation statements)
references
References 10 publications
4
67
0
1
Order By: Relevance
“…Generally, one helical turn of amylose is composed of B6 repeating glucose units when linear molecules with a small cross-sectional area such as fatty acids are included (Figure 3). [42][43][44] The repeat distance of the helix of amylose was reported as B0.80 nm (Figure 3), [42][43][44] whereas the lengths of one GA unit and one CL unit in P(GA-co-CL) were calculated to be B0.36 and 0.84 nm, respectively, using the MM2 routine in the CS Chem 3D program package (Figure 3). On the basis of these values, theoretical ratios of the H 1 protons of amylose to the methylene protons e in GA unit (e/H 1 ) and to the methylene protons a in CL unit (a/H 1 ) were calculated to be 0.16 and 0.25, respectively, (Run 1 in Table 1; refer to the experimental section for a detailed calculation method).…”
Section: Resultsmentioning
confidence: 99%
“…Generally, one helical turn of amylose is composed of B6 repeating glucose units when linear molecules with a small cross-sectional area such as fatty acids are included (Figure 3). [42][43][44] The repeat distance of the helix of amylose was reported as B0.80 nm (Figure 3), [42][43][44] whereas the lengths of one GA unit and one CL unit in P(GA-co-CL) were calculated to be B0.36 and 0.84 nm, respectively, using the MM2 routine in the CS Chem 3D program package (Figure 3). On the basis of these values, theoretical ratios of the H 1 protons of amylose to the methylene protons e in GA unit (e/H 1 ) and to the methylene protons a in CL unit (a/H 1 ) were calculated to be 0.16 and 0.25, respectively, (Run 1 in Table 1; refer to the experimental section for a detailed calculation method).…”
Section: Resultsmentioning
confidence: 99%
“…(4) The crystals formed are characterized by X-ray diffraction peaks with d-spacing of 0.12, 0.68, and 0.44 nm for a hydrated V-amylose (V h ) complex and 1.13, 0.65, and 0.43 nm for an anhydrous V-type (V a ). (4,46,48) The V-amylose crystals are orthogonal structures with dimensions ranging from a = 1.36-1.37 nm, b = 2.37-2.58 nm, and c = 0.78 -0.81 nm. (4,6,46,48) In space, the single helices are organized into the standard orthogonal space group 8 P2 1 2 1 2 1 arrangement and may have up to 4 or 16 water molecules in the interhelical space within each crystal unit cell for V a and V h , respectively ( Figure 2).…”
Section: V-amylose Helix Molecular Arrangementmentioning
confidence: 99%
“…(4,46,48) The V-amylose crystals are orthogonal structures with dimensions ranging from a = 1.36-1.37 nm, b = 2.37-2.58 nm, and c = 0.78 -0.81 nm. (4,6,46,48) In space, the single helices are organized into the standard orthogonal space group 8 P2 1 2 1 2 1 arrangement and may have up to 4 or 16 water molecules in the interhelical space within each crystal unit cell for V a and V h , respectively ( Figure 2). (4,6,10) The 8-fold helices (V8) on the other hand, may occur as tetragonal P41212 or P43212 space group with unit cell parameters a = b = 2.2844 nm and c = 0.7806 nm (49) .…”
Section: V-amylose Helix Molecular Arrangementmentioning
confidence: 99%
“…Zobel et al found that the most probable space symmetry group for V-amylose is the group P2 1 2 1 2 1 . 19 The model of an isolated chain of amylose is represented by a helix with a 6 1 screw axis. The factor group of the 6 1 helix is isomorphic to the point group C 6 .…”
Section: Molecular and Crystal Structures Of Investigated Disaccharidmentioning
confidence: 99%